PENGARUH MOTIVASI BELAJAR, SARANA PRASARANA BELAJAR, DAN KEMAMPUAN MENGAJAR GURU TERHADAP SISWA DI SMPN 1 KECAMATAN. PAGU KABUPATEN. KEDIRI - Erwin Syahputra (Faculty of Social and Political Science, 2015)
Student achievement is influenced by many factors, both internal factors and external factors. One of the internal factors that contribute to the achievement of learning is learning motivation factor, while contributing to the achievement of the Learning Achievement of external factors such as infrastructure learning and teaching capabilities (competencies). This study aimed to determine: (1) Whether or not the effect of learning motivation on learning achievement, (2) Whether or not the effect of Learning Infrastructure on learning achievement, (3) Whether or not the effect of the ability of teachers to teach to the learning achievement, (4) Whether or not the effect between learning motivation, learning infrastructure and the ability of teachers to teach to the learning achievement. The results showed a significant effect between motivation to learn, Learning Infrastructure, and the ability of teachers to teach Learning Achievement. It is based on the coefficient of determination (R2) obtained a value of 0.734 This means that 73.4% variation in the presentation of learning (Y) can be explained by the motivation to learn (X1), learning infrastructure (X2), and the ability of teachers to teach (X3) along together. According results suggested teachers should constantly strive to motivate and encourage students to learn actively, and is expected to increase student learning achievement, school parties should take into considerations in determining school policies in order to improve learning achievement and provides learning facilities to support learning activities . And for the students themselves should further foster motivation to learn so as to improve learning achievement.